Laminate, packaging material, and packaging bag

The laminate structure, featuring a thermosetting coating agent, stretched polyethylene film, and polyethylene heat seal layer, addresses the challenges of recyclability and heat sealing in conventional packaging materials, achieving improved strength, heat resistance, and productivity.

JP2025062580APending Publication Date: 2025-04-14OKURA INDUSTRIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024170328
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-02
Filing Date
2024-09-30
Publication Date
2025-04-14

AI Technical Summary

Technical Problem

Conventional packaging materials made from different resin materials are difficult to recycle due to separation issues, and they suffer from insufficient heat sealing, narrow temperature conditions for bag-making, poor productivity, and inadequate strength, especially in pillow packaging.

Method used

A laminate structure comprising a heat-resistant coating layer made of a thermosetting coating agent, a base material of stretched high-density or medium-density polyethylene film, and a heat seal layer of polyethylene, laminated in that order, to enhance strength, heat resistance, and recyclability.

Benefits of technology

The laminate improves heat resistance during heat sealing, prevents substrate layer adhesion to high-temperature jigs, suppresses wrinkles in the heat seal portion, and enhances heat seal strength, particularly in the vertical direction, thereby expanding suitable bag-making temperature conditions and improving packaging productivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062580000001_ABST
    Figure 2025062580000001_ABST
Patent Text Reader

Abstract

To provide a laminate that can achieve a packaging material having adequate strength and heat resistance applicable as the packaging material, while also offering superior recyclability.SOLUTION: Provided is a laminate having a structure in which a heat-resistant coating layer, a base material, and a heat seal layer are laminated in this order, wherein the heat-resistant coating layer is a layer composed of a thermosetting coating agent, the base material is composed of a stretched film containing high-density polyethylene and / or medium-density polyethylene, and the heat seal layer is composed of polyethylene.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate and a packaging material using the same. More specifically, the present invention relates to a laminate having excellent material recyclability and small environmental impact, and a packaging material using the same. [Background technology]

[0002] Conventionally, packaging materials and the like are produced using resin films made of resin materials. For example, resin films made of polyethylene have appropriate flexibility and transparency as well as excellent heat sealability, and are therefore widely used as packaging materials.

[0003] Normally, a resin film made of polyethylene cannot be used as a substrate because it is inferior in strength and heat resistance, and is instead used by laminating it with a resin film made of polyester or polyamide, etc., and the substrate and heat seal layer are composed of a laminated film made of different types of resin materials.

[0004] In recent years, with the growing demand for the creation of a recycling-oriented society, there has been a demand for packaging materials with high recyclability. However, as described above, conventional packaging materials are composed of different types of resin materials, and it is difficult to separate the individual resin materials, so that they are not currently recycled.

[0005] In view of this, Patent Document 1 describes a laminate in which a stretched film made of polyethylene is used as a base film and the base film is laminated with a heat seal layer also made of polyethylene, and proposes that by using a stretched film made of polyethylene as the base material, a packaging material that has sufficient strength and heat resistance and is also recyclable. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Publication No. 2020-55157 Summary of the Invention [Problem to be solved by the invention]

[0007] In the bag-making process for forming a packaging bag, there is a process in which the heat-sealed layers of the laminate are placed face to face, and the laminate is sandwiched by applying pressure from the outer surface side of the base material layer with a high-temperature tool to thermally weld (heat seal). However, when the laminate described in Patent Document 1 is applied to a packaging bag, the tool of the heat-sealing machine is at a high temperature, and the outer surface side of the base material layer that directly contacts the tool is exposed to high temperature, so in the conventional laminate, problems such as the base material layer being affected by heat and adhering to the tool, or wrinkles occurring in the heat-sealed portion may occur, resulting in insufficient heat sealability, a narrow range of appropriate bag-making temperatures, poor productivity, and insufficient strength of the packaging bag.

[0008] In addition, pillow packaging, which is one type of packaging form, is a method in which a film fed by a roll is formed into a cylindrical shape by a bag making machine, and then a center seal (vertical seal) is applied, and then the contents are filled or loaded while the bottom seal (horizontal seal) and cutting are applied at the same time to package the contents, and since it is possible to package at a relatively high speed, it is widely used. However, when the laminate described in Patent Document 1 is applied, there are problems such as a narrow range of suitable bag making temperatures, particularly for center sealing (vertical seal), insufficient heat sealability, and poor productivity. In pillow packaging, since the center seal of the continuous heat seal has a large effect on productivity, it is important to widen the suitable bag making temperature range for bottom sealing and increase the heat seal strength in order to improve productivity. Furthermore, bags manufactured by pillow packaging have a problem that the vertical seal part is easily torn in a bag drop test, and there is a demand for improving the heat seal strength and impact resistance of the vertical seal. Furthermore, when examining the optimum bag-making temperature conditions, it is necessary to take into account the shrinkage of the heat-sealed parts. If the shrinkage during heat sealing is significant, wrinkles will occur during bag making, so it is necessary to suppress the shrinkage of the heat-sealed parts even over a wide range of optimum bag-making temperature conditions.

[0009] The present invention has been made in consideration of such problems, and has an object to provide a laminate that can realize a packaging material that has sufficient strength and heat resistance to be applicable as a packaging material and is also excellent in recyclability. [Means for solving the problem]

[0010] The inventors have conducted extensive research into a laminate that has sufficient strength and heat resistance to be applicable as a packaging material and also has excellent recyclability. As a result, they have found that the above-mentioned problems can be solved by using a structure in which a heat-resistant coating layer made of a thermosetting coating agent, a substrate made of a stretched film containing high-density polyethylene and / or medium-density polyethylene, and a heat-seal layer made of polyethylene are laminated in this order, and have thus completed the present invention.

[0011] According to the present invention, (1) A laminate is provided, which has a structure in which a heat-resistant coating layer, a substrate, and a heat-sealing layer are laminated in this order, the heat-resistant coating layer being a layer made of a thermosetting coating agent, the substrate being made of a stretched film containing high-density polyethylene and / or medium-density polyethylene, and the heat-sealing layer being made of polyethylene; (2) The laminate according to (1) is provided, characterized in that the thermosetting coating agent contains cellulose acetate, a crosslinking agent and an organic solvent, and the acetylation degree of the cellulose acetate is 40 to 70%, (3) There is provided the laminate according to (1), characterized in that the stretched film is a biaxially stretched film having a stretching ratio of 2 to 10 times in the machine direction (MD) and a stretching ratio of 2 to 10 times in the transverse direction (TD), (4) The laminate according to (1), wherein the elastic modulus in the transverse direction (TD) is higher than the elastic modulus in the longitudinal direction (MD), (5) The laminate according to (1) is provided, characterized in that the content of polyethylene in the entire laminate is 90% by weight or more; (6) There is provided a laminate according to any one of (1) to (5), which is used for a pillow packaging material application, (7) A packaging material is provided, characterized by using the laminate according to any one of (1) to (5), (8) A packaging bag is provided, which is characterized by using the laminate according to any one of (1) to (5). Effect of the Invention

[0012] According to the present invention, by using a thermosetting coating agent as the heat-resistant coating layer, the heat resistance during heat sealing is improved, and it is possible to prevent the base layer from fusing to a high-temperature jig. In addition, by using a biaxially oriented film containing high-density polyethylene and / or medium-density polyethylene as the base material, the occurrence of wrinkles in the heat-sealed portion is suppressed, the heat-sealing strength is improved, and the appropriate conditions for the bag-making temperature can be expanded. In addition, since the heat-sealing strength can be improved especially in the machine direction (MD), it is possible to increase the packaging speed of the center seal in pillow packaging, improve productivity, and prevent the bag from breaking due to dropping, etc. In addition, shrinkage of the heat-sealed portion is suppressed, and a packaging bag with excellent appearance can be obtained. [Brief description of the drawings]

[0013] [Figure 1] 1 is a schematic cross-sectional view illustrating one embodiment of a laminate according to the present invention. [Diagram 2] 2A and 2B are graphs relating to the heat seal strength of the laminate according to the present invention, where FIG. 2A is a graph showing the heat seal strength of vertical seals, and FIG. 2B is a graph showing the heat seal strength of horizontal seals. [Diagram 3] 3A and 3B are graphs relating to the seal shrinkage rate of a laminate according to the present invention, where FIG. 3A is a graph showing the seal shrinkage rate of a vertical seal, and FIG. 3B is a graph showing the seal shrinkage rate of a horizontal seal. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be described in detail below. Note that the present invention is not limited to the following embodiments, and various embodiments can be made within the scope of the effects of the present invention.

[0015] [Laminate] In the first embodiment, as shown in Fig. 1, the laminate 1 of the present invention has a structure in which a heat-resistant coating layer 2, a substrate 3, and a heat-seal layer 4 are laminated in this order. In order to enhance the adhesion and bonding between the substrate and the heat-seal layer, an extruded resin layer may be provided between the substrate and the heat-seal layer via an anchor coat layer as necessary, and the substrate and the heat-seal layer may be extrusion laminated. Alternatively, an adhesive layer may be provided between the substrate and the heat-seal layer, and the substrate and the heat-seal layer may be dry laminated.

[0016] In the laminate of the present invention, the polyethylene content is preferably 90% by weight or more. By making the polyethylene content in the entire laminate 90% by weight or more, the recyclability of the laminate of the present invention can be improved. The polyethylene content in the entire laminate is more preferably 91% by weight or more, even more preferably 92% by weight or more, particularly preferably 93% by weight or more, and most preferably 95% by weight or more.

[0017] In the laminate of the present invention, it is preferable that the elastic modulus of the laminate in the transverse direction (TD) is higher than that in the longitudinal direction (MD). If the elastic modulus in TD is higher than that in MD, the heat seal strength in MD can be improved. Although the reason for this is unclear, it is believed that by setting the elastic modulus in MD and TD of the laminate within a specific range, stress such as expansion and contraction of the laminate due to thermal load during heat sealing can be suppressed, uniform heat sealing can be achieved, and appropriate stiffness is created in the laminate, increasing its strength against stress in the tensile direction.

[0018] In the laminate of the present invention, the TD elastic modulus of the laminate is preferably 200 MPa to 1000 MPa, more preferably 300 MPa to 900 MPa, even more preferably 400 MPa to 800 MPa, and particularly preferably 500 MPa to 700 MPa. The MD elastic modulus of the laminate is preferably 200 MPa to 1000 MPa, more preferably 300 MPa to 900 MPa, even more preferably 400 MPa to 700 MPa, and particularly preferably 450 MPa to 600 MPa.

[0019] Each layer constituting the laminate of the present invention will now be described.

[0020] [Heat-resistant coating layer] The heat-resistant coating layer is provided to prevent defects during heat sealing during bag making and filling and sealing, and ensures heat-sealing suitability, and is characterized by being composed of a thermosetting coating agent to impart heat resistance that does not cause softening, melting, decomposition, etc. during heat sealing. This composition improves heat resistance during heat sealing, suppresses fusion of the substrate to the seal bar, and suppresses the occurrence of wrinkles in the heat-sealed portion, thereby improving heat-sealing strength.

[0021] The thermosetting coating agent is a thermosetting coating agent containing at least a resin component, a crosslinking agent, and a solvent, and examples thereof include a dispersion in which the resin component is dispersed in water, and a coating liquid in which the resin component is dissolved in an organic solvent, and the resin component is preferably at least one resin selected from the group consisting of cellulose acetate, polyurethane, polyester, polyamide, polyamideimide, and epoxy. After applying a thermosetting coating agent containing these components onto a substrate, the solvent is evaporated to dry and cure the coating agent, thereby forming a heat-resistant coating layer.

[0022] The thermosetting coating agent is preferably a cellulose acetate-based coating agent, since it can impart extremely high heat resistance to the heat-sealable laminate, and the cellulose acetate-based coating agent contains cellulose acetate, a crosslinking agent, and an organic solvent. Cellulose acetate is a semi-synthetic polymer obtained by acetic esterification of cellulose, which is a natural polymer. Cellulose is a polymer with anhydroglucose as a repeating unit, and has three hydroxyl groups per repeating unit. Depending on the degree of esterification (substitution degree), cellulose acetate resins with different properties can be obtained. The substitution degree is expressed as an index called the acetylation degree. The acetylation degree of cellulose in which all three hydroxyl groups are acetylated, i.e., triacetyl cellulose, is 62.5%. The acetylation degree of the cellulose acetate used in the present invention is preferably 40 to 70%, more preferably 43 to 62%. The average polymerization degree is preferably about 100 to 400.

[0023] The content of cellulose acetate in the cellulose acetate-based coating agent is preferably 5% by weight or more, and more preferably 10% by weight or more, in terms of solid content excluding organic solvents.

[0024] As the crosslinking agent in the cellulose acetate coating agent, an isocyanate compound capable of reacting with unsubstituted hydroxyl groups is preferred. As the isocyanate compound, various compounds can be used, such as 1,4-tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate, 1,12-dodecamethylene diisocyanate, cyclohexane-1,3- or 1,4-diisocyanate, 1-isocyanato-3-isocyanatomethyl-3,5,5-trimethylcyclohexane (also known as isophorone diisocyanate; IPDI), dicyclohexylmethane-4,4'-diisocyanate (also known as hydrogenated MDI), 2- or 4-isocyanatocyclohexyl-2'-isocyanatocyclohexylmethane, 1,3- or 1,4-bis-(isocyanatomethyl)-cyclohexane, bis-(4-isocyanato- 3-methylcyclohexyl)methane, 1,3- or 1,4-α,α,α'α'-tetramethylxylylene diisocyanate, 2,4- or 2,6-diisocyanatotoluene, 2,2'-,2,4'- or 4,4'-diisocyanatodiphenylmethane (MDI), 1,5-naphthalene diisocyanate, p- or m-phenylene diisocyanate, xylylene diisocyanate, or diphenyl-4,4'-diisocyanate. Among these, aromatic diisocyanates are preferable when mechanical strength is considered, and aliphatic or alicyclic diisocyanate compounds are preferable when durability and light resistance are considered. In addition, aromatic diisocyanates are preferable because they can easily obtain suitable adhesion to the printing layer, and MDI-based polyisocyanates are particularly preferable when a cellulose acetate-based coating agent is applied to the printing layer.

[0025] In order to further improve the heat resistance of the heat-resistant coating layer, it is acceptable to use a crosslinking agent such as an amino resin, an epoxy compound, an aziridine compound, a carbodiimide compound, or an oxazoline compound. Among them, an amino resin such as a melamine crosslinking agent or an isocyanate compound is most preferable because of its fast reactivity. It is also acceptable to use two or more crosslinking agents or to use an appropriate amount of a curing accelerator.

[0026] The amount of the crosslinking agent added is preferably 1 to 20 parts by weight, more preferably 3 to 10 parts by weight, based on 100 parts by weight of the solid content of the cellulose acetate coating agent. Within this range, it is possible to improve blocking resistance, heat resistance, moist heat resistance, and solvent resistance without impairing the suitability when performing printing or the like on the heat-resistant coating layer. In particular, when an isocyanate-based crosslinking agent is used as the crosslinking agent, it is preferable to use 5 parts by weight or more of the isocyanate-based crosslinking agent based on 100 parts by weight of the solid content of the cellulose acetate coating agent.

[0027] As the organic solvent in the cellulose acetate coating agent, it is preferable to use an organic solvent having a boiling point of 150°C or less, in consideration of removing the residual solvent contained in the coating layer. Examples of organic solvents having a boiling point of 150°C or less include MEK (methyl ethyl ketone), benzene, toluene, ethyl acetate, acetone, methyl ethyl ketone, diethyl ether, tetrahydrofuran, methyl acetate, acetonitrile, chloroform, and methylene chloride. These can be used alone or in combination. Among these, it is particularly preferable to use acetone, methyl ethyl ketone, toluene, and ethyl acetate as solvents having high solubility for the cellulose acetate coating agent.

[0028] The cellulose acetate coating agent may contain organic polymers and synthetic rubber resin components such as nitrocellulose, vinyl chloride-vinyl acetate copolymers, vinyl chloride-vinyl acetate-vinyl alcohol copolymers, urethane resins, fluorine resins, acrylic resins, epoxy resins, and polybutyral resins, together with cellulose acetate. Furthermore, additives such as lubricant components, inorganic fine particles, and antistatic agents may be added within a range that does not impair heat resistance.

[0029] The thickness of the heat-resistant coating layer is not particularly limited, but from the viewpoint of maintaining a practical level of heat resistance and good production efficiency, it is preferably, for example, 0.2 μm or more and 50 μm or less, and taking into consideration the adhesion to the seal bar and the coating strength, it is more preferably 0.5 μm or more and 10 μm or less.

[0030] [Base material] The substrate is characterized by being composed of a stretched film containing high density polyethylene (HDPE) and / or medium density polyethylene (MDPE). This configuration improves the recyclability of the laminate, suppresses the occurrence of wrinkles in the heat-sealed portion, and improves the heat-seal strength. It also improves the heat-seal strength in the machine direction (MD). Note that the stretched film referred to here is a film whose shrinkage stress has been relaxed by heat treatment or the like after stretching, and is different from a "heat-shrinkable film" that is used by shrinking it by heat.

[0031] The stretched film may be either a uniaxially stretched film or a biaxially stretched film, but is preferably a biaxially stretched film from the viewpoints of hand tearability, strength, and heat resistance.

[0032] The stretching ratio in the machine direction (MD) of the stretched film is preferably 2 to 10 times, more preferably 3 to 7 times. By making the stretching ratio in the machine direction (MD) of the stretched film 2 times or more, the strength and heat resistance of the laminate of the present invention can be improved. The upper limit of the stretching ratio in the machine direction (MD) of the stretched film is not particularly limited, but it is preferably 10 times or less from the viewpoint of the breaking limit of the stretched film.

[0033] The stretching ratio in the transverse direction (TD) of the stretched film is preferably 2 to 10 times, and more preferably 3 to 7 times. By making the stretching ratio in the transverse direction (TD) of the stretched film 2 times or more, the strength and heat resistance of the laminate of the present invention can be improved. The upper limit of the stretching ratio in the transverse direction (TD) of the stretched film is not particularly limited, but is preferably 10 times or less from the viewpoint of the breaking limit of the stretched film.

[0034] The polyethylene contained in the base material has a density of 0.945 g / cm 3 High density polyethylene (HDPE), with a density of 0.925g / cm 3 More than 0.945g / cm 3 A medium density polyethylene (MDPE) having a density of less than 1000 nm can be used, and these can be used alone or in a blend. In addition, low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and very low density polyethylene (VLDPE) can be included as other polyethylene components, and when other polyethylene components are included, it is preferable to include the total amount of HDPE and MDPE as the main component. Here, the main component means that the composition ratio of the components constituting the base material is 50% by weight or more, preferably 60% by weight or more, more preferably 80% by weight or more, even more preferably 90% by weight or more, and particularly preferably 95% by weight or more.

[0035] The thickness of the substrate is not particularly limited, but is preferably 10 μm or more and 50 μm or less, and more preferably 12 μm or more and 30 μm or less. By making the thickness of the substrate 10 μm or more, the strength of the laminate of the present invention can be improved. In addition, by making the thickness of the substrate 50 μm or less, the processability of the laminate of the present invention can be improved.

[0036] The substrate can be prepared by forming a film from polyethylene by a T-die method or an inflation method, and then stretching the film. When the substrate is prepared by the T-die method, the MFR of the polyethylene is preferably 3 g / 10 min or more and 20 g / 10 min or less. By making the MFR of the polyethylene 3 g / 10 min or more, the processability of the laminate of the present invention can be improved. In addition, by making the MFR of the polyethylene 20 g / 10 min or less, the resin film can be prevented from breaking. When the substrate is prepared by the inflation method, the MFR of the polyethylene is preferably 0.5 g / 10 min or more and 5 g / 10 min or less. By making the MFR of the polyethylene 0.5 g / 10 min or more, the processability of the laminate of the present invention can be improved. In addition, by making the MFR of the polyethylene 5 g / 10 min or less, the film formability can be improved. The substrate is not limited to those prepared by the above method, and commercially available ones may be used.

[0037] The substrate may contain additives within the range that does not impair the characteristics of the present invention. Examples of such additives include crosslinking agents, antioxidants, antiblocking agents, slip agents, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.

[0038] The substrate may be surface-treated. This can improve adhesion to adjacent layers. The method of surface treatment is not particularly limited, and examples thereof include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment, as well as chemical treatments such as oxidation treatment using chemicals.

[0039] The substrate may have a printed layer on its surface, and the image formed on the printed layer is not particularly limited, and may represent characters, patterns, symbols, or combinations thereof. The method for forming the printed layer is not particularly limited, and may include conventionally known printing methods such as gravure printing, offset printing, and flexographic printing. Among these, flexographic printing is preferred from the viewpoint of environmental load.

[0040] The substrate may have a gas barrier layer on its surface. This can improve the gas barrier properties of the laminate, specifically the oxygen barrier properties and water vapor barrier properties. Examples of the gas barrier layer include deposition films made of metals such as aluminum, and inorganic oxides such as aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, and barium oxide, and coating films of gas barrier resins such as ethylene-vinyl alcohol copolymers (EVOH), polyvinyl alcohol, polyacrylonitrile, polyamides such as nylon 6, nylon 6,6, and polymetaxylylene adipamide (MXD6), polyesters, polyurethanes, and (meth)acrylic resins.

[0041] The thickness of the vapor-deposited film is preferably 1 nm or more and 150 nm or less, more preferably 5 nm or more and 60 nm or less, and even more preferably 10 nm or more and 40 nm or less. By making the thickness of the vapor-deposited film 1 nm or more, the oxygen barrier property and water vapor barrier property of the laminate can be further improved. In addition, by making the thickness of the vapor-deposited film 150 nm or less, the occurrence of cracks in the vapor-deposited film can be prevented. In addition, the recyclability of the laminate can be maintained.

[0042] The thickness of the barrier coat layer is preferably 0.01 μm or more and 10 μm or less, and more preferably 0.1 μm or more and 5 μm or less. By making the thickness of the barrier coat layer 0.01 μm or more, the oxygen barrier property and water vapor barrier property of the laminate can be further improved. By making the thickness of the barrier coat layer 10 μm or less, the recyclability of the laminate can be maintained. The barrier coat layer can be formed by dissolving or dispersing the above-mentioned material in water or a suitable solvent, applying and drying. The barrier coat layer can also be formed by applying and drying a commercially available barrier coat agent.

[0043] [Heat seal layer] The heat seal layer is characterized by being made of polyethylene, which makes it possible to produce a packaging material that has sufficient strength and heat resistance and is also recyclable.

[0044] From the viewpoint of heat sealability, the polyethylene constituting the heat seal layer is preferably low density polyethylene (LDPE), linear low density polyethylene (LLDPE) or very high density polyethylene (VLDPE). Copolymers of ethylene and other monomers can be used as long as they do not impair the characteristics of the present invention. Moreover, from the viewpoint of environmental load, biomass-derived polyethylene or recycled polyethylene is preferable.

[0045] The thickness of the heat seal layer is not particularly limited, and is preferably changed appropriately according to the weight of the contents to be filled in the packaging material produced by the laminate of the present invention. For example, when producing a packaging bag filled with contents of 1 g or more and 200 g or less, the thickness of the heat seal layer is preferably 20 μm or more and 60 μm or less. By making the heat seal layer thicker than 20 μm, the filled contents can be prevented from leaking due to damage to the heat seal layer. In addition, by making the heat seal layer thicker than 60 μm, the processability of the laminate of the present invention can be improved. In addition, for example, when producing a stand pouch filled with contents of 50 g or more and 2000 g or less, the thickness of the heat seal layer is preferably 50 μm or more and 200 μm or less. By making the heat seal layer thicker than 50 μm, the filled contents can be prevented from leaking due to damage to the heat seal layer. In addition, by making the heat seal layer thicker than 200 μm, the processability of the laminate of the present invention can be improved.

[0046] [Anchor coat layer] The anchor coat layer is provided to increase the adhesive strength between the substrate side and the extruded resin layer when the substrate and the heat seal layer are extrusion laminated, and is formed by applying an anchor coat agent to the substrate side and drying (curing). The anchor coat layer can use a conventionally known anchor coat agent, and is not particularly limited, but examples thereof include polyethylene-based, isocyanate-based, polyethyleneimine-based, polybutadiene-based, etc. Among these, polyethylene-based agents containing polyethylene polymers are preferred from the viewpoint of recyclability of the laminate.

[0047] The polyethylene polymer preferably contains an ethylene component and a component derived from an unsaturated carboxylic acid and / or its acid anhydride as copolymerization components. The content of the ethylene component in the polyethylene polymer is preferably 50% by weight or more and 95% by weight or less, more preferably 55% by weight or more and 94.5% by weight or less. This can improve the adhesion between the substrate and the heat seal layer, and can also improve the aqueous dispersibility of the polyethylene polymer. Also, the resistance to contents can be improved.

[0048] The unsaturated carboxylic acids contained in the polyethylene polymer include (meth)acrylic acid, maleic acid, itaconic acid, fumaric acid, and crotonic acid.

[0049] As long as the characteristics of the present invention are not impaired, the polyethylene polymer may contain components (other components) other than the ethylene component and the unsaturated carboxylic acid component. Examples of the other components include propylene, 1-butene, isobutene, 1-pentene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-hexene, 1-octene, butadiene, isoprene, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, dimethyl maleate, diethyl maleate, dibutyl maleate, methyl vinyl ether, ethyl vinyl ether, vinyl formate, vinyl acetate, and vinyl propionate.

[0050] In the polyethylene polymer, the copolymerization form of each component is not limited, and examples thereof include random copolymerization, block copolymerization, and graft copolymerization. Among these, random copolymerization is preferred from the viewpoint of ease of polymerization.

[0051] The thickness of the anchor coat layer is not particularly limited, but is preferably 0.01 μm or more and 3 μm or less, more preferably 0.05 μm or more and 1 μm or less, and even more preferably 0.1 μm or more and 0.5 μm or less. If the thickness is thinner than the above range, the adhesive strength may be small and the effect may not be exerted. If the thickness is thicker than the above range, it leads to an increase in cost and is not preferable from the viewpoint of the recyclability of the laminate.

[0052] [Extruded resin layer] The extruded resin layer is provided to bond the substrate and the heat seal layer by extrusion lamination, and is preferably made of polyethylene. By using such a configuration, a packaging material having sufficient strength and heat resistance and being recyclable can be produced.

[0053] The polyethylene constituting the extruded resin layer is preferably low density polyethylene (LDPE), linear low density polyethylene (LLDPE) or very high density polyethylene (VLDPE). Copolymers of ethylene and other monomers can be used as long as they do not impair the characteristics of the present invention. From the viewpoint of environmental load, biomass-derived polyethylene or recycled polyethylene is preferable.

[0054] The thickness of the extruded resin layer is not particularly limited, but is preferably, for example, 1 μm or more and 60 μm or less, more preferably 5 μm or more and 50 μm or less, and even more preferably 10 μm or more and 30 μm or less.

[0055] The extruded resin layer can be formed by melting the polyethylene and extruding it onto the substrate. The melting temperature at this time is not particularly limited, but is preferably 280°C or higher and 330°C or lower.

[0056] [Adhesive layer] The adhesive layer is provided to bond the substrate and the heat seal layer by dry lamination, and preferably contains at least one adhesive, which can improve the adhesion between the layers.

[0057] The adhesive layer can be a conventionally known adhesive, and may be a one-component curing type, a two-component curing type, or a non-curing type. The adhesive may be a solvent-free adhesive or a solvent-based adhesive, but from the viewpoint of environmental load, a solvent-free adhesive is preferably used.

[0058] Examples of solventless adhesives include polyether adhesives, polyester adhesives, silicone adhesives, epoxy adhesives, and urethane adhesives, and among these, two-liquid curing urethane adhesives are preferably used. Examples of solvent-based adhesives include rubber adhesives, vinyl adhesives, silicone adhesives, epoxy adhesives, phenol adhesives, and olefin adhesives.

[0059] The thickness of the adhesive layer is preferably 0.5 μm or more and 6 μm or less, more preferably 0.8 μm or more and 5 μm or less, and even more preferably 1 μm or more and 4.5 μm or less. By making the thickness of the adhesive layer 0.5 μm or more, the adhesiveness of the adhesive layer can be improved. In addition, when an adhesive layer made of a cured product of a resin composition containing a polyester polyol, an isocyanate compound, and a phosphoric acid-modified compound is provided adjacent to an aluminum vapor deposition film, the bending load resistance of the laminate can be improved. By making the thickness of the adhesive layer 6 μm or less, the processability of the laminate can be improved.

[0060] The adhesive layer can be formed by coating on a substrate or the like and drying using a conventional method such as direct gravure roll coating, gravure roll coating, kiss coating, reverse roll coating, Fontaine method, and transfer roll coating.

[0061] [Packaging materials] The packaging material of the present invention is characterized in that it is composed of the above-mentioned laminate.

[0062] In one embodiment, the bag-shaped packaging material can be produced by folding the laminate of the present invention in half, overlapping the laminate with the heat seal layer on the inside, and heat sealing the ends. In one embodiment, the bag-shaped packaging material can also be produced by overlapping two laminates with the heat seal layers facing each other, and heat sealing the ends.

[0063] In another embodiment, the bag-shaped packaging form can be produced by forming the film of the laminate of the present invention fed from a film roll into a cylindrical shape using a bag-making machine so that the heat seal layer is on the inside, followed by center sealing, and then filling or loading the contents while sealing the bottom and simultaneously cutting to package the contents.

[0064] The heat sealing method is not particularly limited, and can be performed by a known method such as bar sealing, rotary roll sealing, belt sealing, impulse sealing, high frequency sealing, ultrasonic sealing, etc.

[0065] The contents filled in the packaging material are not particularly limited, and may be liquid, powder, or gel. The contents may be food or non-food. After filling with the contents, the opening is heat-sealed to form a package. EXAMPLES

[0066] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0067] The measurement and evaluation methods carried out for each laminate are as follows. (Elasticity Modulus) The samples cut to a size of 190 mm x 15 mm were measured (n=7) using an autograph AGS-500NX (Shimadzu Corporation) at a tensile speed of 5.0 mm / min and a chuck distance of 50 mm, and the average was taken as the measured value. The measurement temperature was 23°C. Both the MD and TD of the film were measured. (Evaluation of heat sealability) The laminate was stacked with the MD and TD aligned, and heat sealed with a 10 mm wide hot plate at a sealing time of 1 second and a sealing pressure of 0.4 MPa (gauge pressure of 0.2 MPa). At this time, the temperature of the lower hot plate was not heated, and the temperature of the upper hot plate was changed from 120°C to 180°C. At this time, the substrate layer was visually inspected to see if it was attached to the heat seal jig, and was evaluated according to the following criteria. ○: No adhesion of the base layer to the heat heel jig is observed ×: Adhesion of the base layer to the heat seal tool is observed. Next, a test piece with a width of 15 mm and an expanded length of 100 mm was prepared from the sealed film, and the heat seal strength was measured according to the heat seal strength test for bags in JIS Z 0238:1998. The distance between the chucks was 40 mm, and the pulling speed was 300 mm / min. The heat seal direction was changed, and the heat seal strength of the vertical seal and the horizontal seal were measured. (Seal shrinkage rate evaluation) The laminate was stacked with the MD and TD aligned, and heat sealed with a 10 mm wide hot plate at a sealing time of 1 second and a sealing pressure of 0.4 MPa (gauge pressure of 0.2 MPa). At this time, the temperature of the lower hot plate was not heated, and the temperature of the upper hot plate was changed from 120°C to 180°C, and the seal shrinkage rate of the heat sealed part was measured. The dimension of the heat sealed part before heat sealing was 30 mm. Sealing shrinkage rate (%) = ((dimension of heat-sealed part after heat-sealing - dimension of heat-sealed part before heat-sealing) / dimension of heat-sealed part before heat-sealing)) x 100

[0068] Example 1 A biaxially oriented high-density polyethylene film (JK Materials' "BOPE film", thickness: 25 μm) was prepared as a substrate, and a cellulose acetate-based coating agent (DIC's "DH-S004 / DH-HARDENER P-60") was applied to one surface and dried to form a heat-resistant coating layer with a thickness of 2 μm. Next, a non-oriented linear low-density polyethylene film (Futamura Chemical's "LL-XLTN", thickness 30 μm) was extrusion laminated to the other surface with low-density polyethylene (Tosoh's "Petrothene 203") to a thickness of 15 μm, to produce a laminate consisting of a heat-resistant coating layer / substrate / extruded resin layer / heat seal layer. The results of evaluation of the elastic modulus, adhesion to a heat seal jig, heat seal strength, and seal shrinkage rate of the obtained laminate are shown in Table 1. The heat seal strength of vertical seals is shown in Figure 2(a), the heat seal strength of horizontal seals in Figure 2(b), the seal shrinkage rate of vertical seals in Figure 3(a), and the seal shrinkage rate of horizontal seals in Figure 3(b).

[0069] Comparative Example 1 A laminate having a structure of substrate / extruded resin layer / heat seal layer was prepared in the same manner as in Example 1, except that no heat-resistant coating layer was provided. The results of evaluation of the elastic modulus, adhesion to a heat seal jig, heat seal strength, and seal shrinkage of the obtained laminate are shown in Table 1. The heat seal strength of the vertical seal is shown in Figure 2(a), the heat seal strength of the horizontal seal in Figure 2(b), the seal shrinkage of the vertical seal in Figure 3(a), and the seal shrinkage of the horizontal seal in Figure 3(b).

[0070] Comparative Example 2 A laminate having a heat-resistant coating layer / substrate / extruded resin layer / heat seal layer configuration was prepared in the same manner as in Example 1, except that a biaxially oriented linear low-density polyethylene film (BOPE film manufactured by Kunshan Jiapu Packaging Materials Co., Ltd., thickness: 25 μm) was used as the substrate. The elastic modulus, adhesion to the heat seal jig, heat seal strength, and seal shrinkage of the obtained laminate are shown in Table 1. The heat seal strength of the vertical seal is shown in FIG. 2(a), the heat seal strength of the horizontal seal is shown in FIG. 2(b), the seal shrinkage of the vertical seal is shown in FIG. 3(a), and the seal shrinkage of the horizontal seal is shown in FIG. 3(b).

[0071] Comparative Example 3 A laminate having a structure of substrate / extruded resin layer / heat seal layer was prepared in the same manner as in Comparative Example 2, except that no heat-resistant coating layer was provided. The results of evaluation of the elastic modulus, adhesion to a heat seal jig, heat seal strength, and seal shrinkage of the obtained laminate are shown in Table 1. The heat seal strength of the vertical seal is shown in Figure 2(a), the heat seal strength of the horizontal seal in Figure 2(b), the seal shrinkage of the vertical seal in Figure 3(a), and the seal shrinkage of the horizontal seal in Figure 3(b).

[0072] [Table 1]

[0073] As shown in Table 1, the laminate of Example 1, which uses a thermosetting coating agent as the heat-resistant coating layer and a biaxially oriented film containing high density polyethylene and / or medium density polyethylene as the substrate, exhibits results in which adhesion of the substrate to the heat-sealing tool is suppressed, and the heat-sealing strength is excellent under a wide range of temperature conditions, and the heat-sealing strength in the machine direction (MD) is particularly excellent. In addition, the shrinkage rate of the heat-sealed portion is small, and wrinkles in the heat-sealed portion are suppressed.

[0074] On the other hand, as shown in Table 1, the laminate of Comparative Example 1, which does not have a heat-resistant coating layer, showed excellent heat-seal strength under a relatively wide range of temperature conditions, although the heat-seal strength in the longitudinal direction was inferior to that of the laminate of Example 1. However, the substrate was found to adhere to the heat-sealing tool, and the laminate did not have sufficient strength and heat resistance to be applicable as a packaging material. The laminate of Comparative Example 2, which has a heat-resistant coating layer and uses a biaxially oriented film made of linear low-density polyethylene as the substrate, showed results in which the heat-seal strength was insufficient, particularly in the MD, and did not have sufficient strength and heat resistance to be applicable as a packaging material. In addition, the shrinkage rate of the heat-sealed portion was large, and wrinkles occurred in the heat-sealed portion. Furthermore, the laminate of Comparative Example 3, which does not have a heat-resistant coating layer and uses a biaxially oriented film made of linear low-density polyethylene as the substrate, showed results in which the substrate was adhered to the heat-sealing tool, and showed results in which the heat-seal strength was insufficient, particularly in the MD, and did not have sufficient strength and heat resistance to be applicable as a packaging material. In addition, the shrinkage rate of the heat-sealed portion was large, and wrinkles occurred in the heat-sealed portion. [Industrial Applicability]

[0075] As described above, the laminate obtained by the present invention can prevent the base layer from fusing to a high-temperature tool, suppresses the occurrence of wrinkles in the heat-sealed portion, has a wide range of suitable bag-making temperatures, and has excellent heat-seal strength, so it can be suitably used as various conventionally known packaging materials. In addition, since it has excellent heat-seal strength in the longitudinal direction (MD), it can be suitably used for pillow packaging and the like, which require heat-seal strength and impact resistance for vertical seals. [Explanation of symbols]

[0076] 1. Laminate 2 Heat-resistant coating layer 3 Base material 4 Heat seal layer

Claims

1. A heat-resistant coating layer, a substrate, and a heat seal layer are laminated in this order. the heat-resistant coating layer is a layer made of a thermosetting coating agent, The substrate is made of a stretched film containing high density polyethylene and / or medium density polyethylene, The laminate, wherein the heat seal layer is made of polyethylene.

2. 2. The laminate according to claim 1, wherein the thermosetting coating agent contains cellulose acetate, a crosslinking agent and an organic solvent, and the acetylation degree of the cellulose acetate is 40 to 70%.

3. 2. The laminate according to claim 1, wherein the stretched film is a biaxially stretched film having a stretching ratio of 2 to 10 times in the machine direction (MD) and a stretching ratio of 2 to 10 times in the transverse direction (TD).

4. 2. The laminate of claim 1, wherein the laminate has a modulus of elasticity in the transverse direction (TD) greater than the modulus of elasticity in the longitudinal direction (MD).

5. 2. The laminate according to claim 1, wherein the content of polyethylene in the entire laminate is 90% by weight or more.

6. 6. The laminate according to claim 1, which is used for pillow packaging material applications.

7. A packaging material comprising the laminate according to any one of claims 1 to 5.

8. A packaging bag comprising the laminate according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Laminate, packaging material, packaging bag and stand pouch

    JP2020055157A